ANALISIS PARTISIPASI POLITIK PEREMPUAN DALAM PERSPEKTIF HUKUM ISLAM - Asiyah Asiyah; Andri Astuti; Nuraini Nuraini (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2021)
The title of this paper is about women’s representation in parliament on islamic perspective. This discussion aims to look beyond the problem involvement of women in parliament, where the government sets the rules of 30% representation of women in parliament, then discuss in Islamic perspective. After conducting in-depth research paper and analysis, the authors concluded 30% representation of women in parliament is set formally in the constitution, while according to Islamic perspective, rule of 30% representation of women in parliament is not contrary to the principles of Islam as it adheres to equality between men and women in leadership issues for women are possessed quality and capability as a leader.